Creutzfeldt–Jakob Disease: Analysis of Four Cases - Al Balushi, Ali; Meeks, Marshall W.; Hayat, Ghazala; Kafaie, Jafar (Frontiers in Neurology, 2016)
Background: Creutzfeldt-Jakob disease (CJD) is a rare, rapidly progressive neurodegenerative disease that almost always results in death in under a year from onset of symptoms. Here, we report four cases of CJD with different clinical presentations diagnosed at our institution over two-year period. Cases: The first patient is an 82-year-old woman who presented with depression, cognitive decline and word-finding difficulty over 4 weeks. The patient deteriorated neurologically to akinetic mutism and death within 6 weeks of presentation. The second patient is a 54-year-old woman with liver cirrhosis who presented with confusion, ataxia and multiple falls over 4 weeks. She was treated initially for hepatic encephalopathy, but continued to progress to mutism, startle myoclonus and obtundation. Death occurred within 4 weeks of presentation. The third patient is a 58-year-old woman who presented with an 8-week history of confusion, urinary incontinence, Parkinsonism, ataxia and myoclonus. Death occurred within 2 months from presentation. The fourth patient is a 67-year-old man who presented with a 6-week history of headache, blurred vision, ataxia and personality change and progressed to confusion, myoclonus, akinetic mutism and obtundation. Death occurred within 3 weeks from presentation. Conclusion: These 4 cases highlight the varied possible clinical presentations of CJD and demonstrate the importance of considering CJD in patients with atypical presentations of rapidly progressive cognitive decline. To diagnose CJD, brain biopsy remains the gold standard. However, the presence of CSF protein 14-3-3, typical MRI findings and suggestive EEG abnormalities all support the diagnosis.